Sisters like us [large type] - Mallery, Susan (Mallery, Susan. Mischief Bay., 2018)
"Divorce left Harper Szymanski with a name no one can spell, a house she can't afford and a teenage daughter who's pulling away. With her fledgling virtual-assistant business, she's scrambling to maintain her overbearing mother's ridiculous standards and still pay the bills, thanks to clients like Lucas, the annoying playboy cop who claims he hangs around for Harper's fresh-baked cookies. Spending half her life in school hasn't prepared Dr. Stacey Bloom for her most daunting challenge--motherhood. She didn't inherit the nurturing gene like Harper and is in deep denial that a baby is coming. Worse, her mother will be horrified to learn that Stacey's husband plans to be a stay-at-home dad ... assuming Stacey can first find the courage to tell Mom she's already six months pregnant. Separately they may be a mess, but together Harper and Stacey can survive anything--their indomitable mother, overwhelming maternity stores and exes' weddings." --